2017
DOI: 10.1021/acs.nanolett.6b05134
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Water-Coupled Metallic MoS2 with Nanochannels for Ultrafast Supercapacitors

Abstract: MoS is a promising electrode material for energy storage. However, the intrinsic multilayer pure metallic MoS (M-MoS) has not been investigated for use in supercapacitors. Here, an ultrafast rate supercapacitor with extraordinary capacitance using a multilayer M-MoS-HO system is first investigated. Intrinsic M-MoS with a monolayer of water molecules covering both sides of nanosheets is obtained through a hydrothermal method with water as solvent. The super electrical conductivity of the as-prepared pure M-MoS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
227
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 367 publications
(239 citation statements)
references
References 28 publications
10
227
1
1
Order By: Relevance
“…Pan et al reported that metallic MoS 2 can also be fabricated by Na 2 MoO 4 •2H 2 O and L‐cysteine in a mixed solvent of DMF and water with a DMF to water ratio of 1.5:1 at 200 °C for 12 h (Figure b). The layer distance of the as‐prepared metallic MoS 2 is around ≈0.90 nm that is much larger than the traditional layer distance of ≈0.62 nm . Song et al proved that metallic MoS 2 could also be achieved by solvothermal method in the mixture of DMF and water of 1:50 .…”
Section: Fabrication Methods For Metallic Mos2mentioning
confidence: 99%
See 2 more Smart Citations
“…Pan et al reported that metallic MoS 2 can also be fabricated by Na 2 MoO 4 •2H 2 O and L‐cysteine in a mixed solvent of DMF and water with a DMF to water ratio of 1.5:1 at 200 °C for 12 h (Figure b). The layer distance of the as‐prepared metallic MoS 2 is around ≈0.90 nm that is much larger than the traditional layer distance of ≈0.62 nm . Song et al proved that metallic MoS 2 could also be achieved by solvothermal method in the mixture of DMF and water of 1:50 .…”
Section: Fabrication Methods For Metallic Mos2mentioning
confidence: 99%
“…The main two MoS 2 phases, metallic 1T phase and semiconducting 2H phase, due to the distinct structures, exhibit noticeable difference in their physical and chemical properties, especially the conductivity properties, where the metallic phase has ≈10 5 times electrical conductivity compared to the semiconducting phase . The low electrical conductivity of semiconducting MoS 2 is disadvantageous for electrochemical energy storage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent electrochemical performances of the M-MoS 2 are attributed to the high electrical conductivity benefiting the charge transfer and the expanded interlayer providing abundant nanochannels for fast diffusion of electrolyte ion. [131] Recently, An and co-workers , respectively and exhibit excellent cycling stability of over 1000 cycles (capacitance retention of 98% and 87% at current densities of 50 A g −1 and 100 A g −1 ). An asymmetric 1T′-MoTe 2 //activated carbon supercapacitor exhibits a maximum specific capacitance of 158.9 F g −1 with an energy density up to 56.4 W h kg −1 .…”
Section: Applications In Pseudocapacitorsmentioning
confidence: 98%
“…Zhu et al develop a hydrothermal route to synthesize metallic MoS 2 (M-MoS 2 ) with expanded nanochannels for ultrafast supercapacitors ( Figure 10G-K). [128,129] XRD analysis in Figure 10G reveals a peak at 7.5° corresponding to an interlayer spacing of 1.18 nm in the wet M-MoS 2 (M-MoS 2 −H 2 O) sample. It can be assigned to (001)-H 2 O for M-MoS 2 −H 2 O, in which a bilayer of water molecules is adsorbed between the adjacent layers of MoS 2 nanosheets, resulting expanded interlayer as nanochannels for ultrafast supercapacitors ( Figure 10I).…”
Section: Applications In Pseudocapacitorsmentioning
confidence: 99%